UTILIZING BLOG IN ELT WRITING TO NON-ENGLISH MAJOR UNDERGRADUATE STUDENTS OF WIRALODRA UNIVERSITY - Anggrarini, Natalia; Wati, Atikah (Universitas Wiralodra, 2019)
Revolutionary Industry 4.0 demands the advanced of technology supports not only in evolutionary level of information and communication, but also in education. Seeking to promote interest of English in higher level of education, this study aims to find out students? experiences in utilizing Blog to learn English especially writing activity. some  researchers have About 15 of Non-English first-grade undergraduate students focusing on Mathematics Education Department will participate in this study. By conducting qualitative research method, questionnaires to 15 students are given to gain the data. The data from questionnaires then be interpreted for the experiences in utilizing blog in English writing activity. The result reveals that blog gave the students a place to share their ideas, exchange ideas, and improve their English as well as their writing ability. Utilizing blog in writing activity also gave them more knowledge about ICT especially in bloging. The findings also lead to some points for the teacher to consider before they utilize blog in writing activity. First, it is about time allocation and second is about involvement of larger number of students. The finding also suggest the teacher to provide longer time in doing blog project and big class is needed to have more meaningful interaction in the blog itself.